A Series of Unfortunate Events: Prinzmetal Angina Culminating in Transmural Infarction in the Setting of Acute Gastrointestinal Hemorrhage - Michael Ruisi; Phillip Ruisi; Hugo Rosero; Paul Schweitzer (Case Reports in Cardiology)
Prinzmetal angina or vasospastic angina is a clinical phenomenon that is often transient and self-resolving. Clinically it is associated with ST elevations on the electrocardiogram, and initially it may be difficult to differentiate from an acute myocardial infarction. The vasospasm induced in this setting occurs in normal or mildly to moderately diseased vessels and can be triggered by a number of etiologies including smoking, changes in autonomic activity, or drug ingestion. While the ischemia induced is usually transient, myocardial infarction and life-threatening arrhythmias can occur in 25% of cases. We present the case of a 65-year-old female where repetitive intermittent coronary vasospasm culminated in transmural infarction in the setting of gastrointestinal bleeding. This case highlights the mortality associated with prinzmetal angina and the importance of recognizing the underlying etiology.